Efectividad de la metodología lean construction en empresas (PYMES) del sector de la construcción en Bogotá (2023)
The research in this monograph reflects the frame of reference resulting from carrying out the review of the literature on the application of the Lean Construction methodology in the management of construction projects of SME companies in Bogotá, this idea aims to obtain high levels of performance, reduction costs, increase in production, compliance in delivery with quality standards, resulting in customer satisfaction; which will help SMEs in the sector to be competitive and sustainable over time by optimally managing construction projects.